2021
DOI: 10.1002/dad2.12199
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility study for detection of retinal amyloid in clinical trials: The Anti‐Amyloid Treatment in Asymptomatic Alzheimer's Disease (A4) trial

Abstract: Introduction The retina and brain exhibit similar pathologies in patients diagnosed with neurodegenerative diseases. The ability to access the retina through imaging techniques opens the possibility for non‐invasive evaluation of Alzheimer's disease (AD) pathology. While retinal amyloid deposits are detected in individuals clinically diagnosed with AD, studies including preclinical individuals are lacking, limiting assessment of the feasibility of retinal imaging as a biomarker for early‐stage AD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 24 publications
0
27
1
Order By: Relevance
“… 4 , 5 , 6 More specifically related to AD pathology, three small studies reported visualization of retinal amyloid beta (Aβ) deposits in vivo using curcumin, a polypotent polyphenol with fluorescent properties that binds to amyloid in post‐mortem brain tissue. 7 , 8 , 9 The presence of retinal amyloid beta deposits is, not unequivocally proven, however, since we and other groups could not confirm amyloid beta deposits in post‐mortem retinal tissue. 10 , 11 , 12 , 13 , 14 Moreover, curcumin is known for its low bioavailability, and although several commercially available formulations enhancing curcumin plasma levels are on the market, so far only one formulation (Longvida) has been reported to visualize retinal amyloid.…”
Section: Introductioncontrasting
confidence: 56%
See 1 more Smart Citation
“… 4 , 5 , 6 More specifically related to AD pathology, three small studies reported visualization of retinal amyloid beta (Aβ) deposits in vivo using curcumin, a polypotent polyphenol with fluorescent properties that binds to amyloid in post‐mortem brain tissue. 7 , 8 , 9 The presence of retinal amyloid beta deposits is, not unequivocally proven, however, since we and other groups could not confirm amyloid beta deposits in post‐mortem retinal tissue. 10 , 11 , 12 , 13 , 14 Moreover, curcumin is known for its low bioavailability, and although several commercially available formulations enhancing curcumin plasma levels are on the market, so far only one formulation (Longvida) has been reported to visualize retinal amyloid.…”
Section: Introductioncontrasting
confidence: 56%
“…Three previous studies showed hyperfluorescence in AD cases after curcumin intake. 7 , 8 , 9 Although these studies were of similar small sample size, AD biomarker confirmation was lacking, which is essential when relating retinal changes to AD, since other structures may cause changes in fluorescence as well. For example, retinal drusen, associated with macular degeneration, contains amyloid and other age‐related deposits.…”
Section: Discussionmentioning
confidence: 99%
“…Aβ deposits in the retina have the potential to be a targeted biomarker for early AD diagnosis and disease progression. The natural compound curcumin binds to Aβ with a high degree of specificity and thus, retinal imaging of fluorescent curcumin has been explored in AD clinical trials and shown promising results ( Koronyo et al, 2017 ; Dumitrascu et al, 2020 ; Ngolab et al, 2021 ). A positive correlation between retinal curcumin-positive spots and brain amyloid has been observed in patients, suggesting that retinal curcumin imaging holds potential for the detection of preclinical AD and the progression of dementia ( Ngolab et al, 2021 ).…”
Section: Microglia In the Ageing Retinamentioning
confidence: 99%
“…The natural compound curcumin binds to Aβ with a high degree of specificity and thus, retinal imaging of fluorescent curcumin has been explored in AD clinical trials and shown promising results ( Koronyo et al, 2017 ; Dumitrascu et al, 2020 ; Ngolab et al, 2021 ). A positive correlation between retinal curcumin-positive spots and brain amyloid has been observed in patients, suggesting that retinal curcumin imaging holds potential for the detection of preclinical AD and the progression of dementia ( Ngolab et al, 2021 ). Regarding the treatment and clearance of amyloid deposits, a recent study has co-cultured brain slices from aged AD mice with young WT mice and has shown that the phagocytic ability of aged microglia can be restored through factors secreted from young microglia, resulting in increased amyloid plaque clearance.…”
Section: Microglia In the Ageing Retinamentioning
confidence: 99%
“…[57,15,2028] However, administrating contrast agents in humans complicates the imaging procedure, hindering its scalability for population screening. To date, only curcumin, a natural fluorochrome, has been tested and used in clinical trials to label retinal Aβ, [6,2123,25] whereas fluorophores used to visualize retinal pTau in vivo are more limited. Therefore, there is an unmet need to develop label-free, high-resolution imaging techniques to visualize retinal Aβ and pTau deposits for early AD screening and disease management.…”
Section: Introductionmentioning
confidence: 99%